2023
DOI: 10.1177/20503121231158220
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of Premaquick biomarkers versus transvaginal cervical length for pre-induction cervical assessment at term among pregnant women

Abstract: Objectives: To compare Premaquick biomarkers (combined insulin-like growth-factor binding protein 1 and interleukin-6) and cervical length measurement via transvaginal ultrasound for pre-induction cervical evaluation at term among pregnant women. Methods: A randomized clinical trial of consenting pregnant women at the Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria. The women were randomized equally into Premaquick group ( n = 36) and transvaginal ultrasound group ( n = 36). The cervix was adjudged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Evidence has revealed that the incidence of preterm labor is globally rising. [1][2][3][4][5][6][7] This can be more keenly felt in this environment due to the lack of sophisticated equipment and technology for enhancing the survival of preterm babies. Therefore, there is a need to stem this tide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has revealed that the incidence of preterm labor is globally rising. [1][2][3][4][5][6][7] This can be more keenly felt in this environment due to the lack of sophisticated equipment and technology for enhancing the survival of preterm babies. Therefore, there is a need to stem this tide.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This represents approximately 10% of all births and is responsible for 75% of perinatal mortality and 50% of long-term morbidity. 5,6 Preterm labor can lead to preterm birth. Preterm birth continues to be the principal reason for global perinatal near-misses and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Induction when successful results in vaginal delivery. Though, it is not free of adverse outcome, IOL is an efficient and safe method of vaginal delivery [ 9 ] . It can sometimes be complicated with potential fetal and maternal risks such as increased rate of abdominal delivery, excessive uterine activity, fetal heart rate abnormalities, uterine rupture, birth asphyxia, intrauterine fetal death (IUFD), maternal water intoxication, preterm delivery due to erroneous estimation of gestational dates, and possible cord prolapse [ 5 , 7 , 10 ]…”
Section: Introductionmentioning
confidence: 99%